2021
DOI: 10.1016/j.lrr.2021.100281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological dose ascorbic acid administration in relapsed refractory multiple myeloma patients

Abstract: Objective High-dose ascorbic acid leads to the formation of highly reactive oxygen species due to the pro-oxidant effect, resulting in cell death; therefore, used as an additive treatment in several malignancies. We present the results obtained by administration of pharmacological dose of ascorbic acid to conventional chemotherapy in relapsed refractory multiple myeloma patients. Materials-methods Intravenous ascorbic acid at a pharmacologic dose of 15 gram/week was add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, in a clinical study reported by Bolaman et al, AA enhanced the cytotoxic effect of carfilzomib-lenalidomide-dexamethasone in relapsed/ refractory myeloma patients who initially did not respond to the treatment; thus AA may have no effect on carfilzomib at pharmacological dose. [193][194][195][196][197][198][199] In a phase I-II clinical trial (NCT01050621), Hoffer et al recommended carrying out trials in higher numbers in order to identify specific clusters of cancer type, chemotherapy regimen and AA combination in which exceptional responses are observed to justify a more focused clinical trial. 196 This position is appropriate.…”
Section: Time For a Second Look?mentioning
confidence: 99%
“…However, in a clinical study reported by Bolaman et al, AA enhanced the cytotoxic effect of carfilzomib-lenalidomide-dexamethasone in relapsed/ refractory myeloma patients who initially did not respond to the treatment; thus AA may have no effect on carfilzomib at pharmacological dose. [193][194][195][196][197][198][199] In a phase I-II clinical trial (NCT01050621), Hoffer et al recommended carrying out trials in higher numbers in order to identify specific clusters of cancer type, chemotherapy regimen and AA combination in which exceptional responses are observed to justify a more focused clinical trial. 196 This position is appropriate.…”
Section: Time For a Second Look?mentioning
confidence: 99%